A safe core mandate - Enrico C. Perotti (Leibniz Institute for Financial Research SAFE, 2023)
Central banks have vastly expanded their footprint on capital markets. At a time of extraordinary pressure by many sides, a simple benchmark for the scale and scope of their core mandate of price and financial stability may be useful. We make a case for a narrow mandate to maintain and safeguard the border between safe and quasi safe assets. This ex-ante definition minimizes ambiguity and discourages risk creation and limit panic runs, primarily by separating market demand for reliable liquidity from risk-intolerant, price-insensitive demand for a safe store of value. The central bank may be occasionally forced to intervene beyond the safe core but should not be bound by any such ex-ante mandate, unless directed to specific goals set by legislation with explicit fiscal support. We review distinct features of liquidity and safety demand, seeking a definition of the safety border, and discuss LOLR support for borderline safe assets such as MMF or uninsured deposits. A safe core formulation is close to the historical focus on regulated entities, collateralized lending and attention to the public debt market, but its specific framing offers some context on controversial issues such as the extent of LOLR responsibilities. It also justifies a persistently large scale for central bank liabilities (Greenwood, Hansom and Stein 2016), as safety demand is related to financial wealth rather than GDP. Finally, it is consistent with an active central bank role in supporting liquidity in government debt markets trading and clearing (Duffie 2020, 2021).
Keywords: 330; Lender of Last Resort; Central Banks; Money Market Funds